EFL Learners’ Proficiency Level of Predicting Word Meaning & Reading Comprehension in Relation to Vocabulary Knowledge - Maysa Abdulkareem Mahmood (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
Words are the main units of any language, without which no effective communication nor learning process take place. Having Insufficient vocabulary knowledge serves as a barrier that keeps pupils from improving their communicative skills and language competence. The aim of this research is to ascertain the relationship between vocabulary knowledge and the reading comprehension and word meaning prediction skills of EFL learners. It is proposed that there is a positive and significant relationship between students’ word knowledge and their capacity to infer word meanings and understand what they read. To accomplish this study, sixty students of the English Department at Baitaxt Institute in the Kurdistan Region-Erbil, were chosen to form thirty freshmen and thirty seniors divided into two groups. There were two tests created and used: the reading comprehension exam and the affixation test. To examine the pertinent data, an Independent T-test and Pearson correlation were performed. Findings of the study revealed that Pupils with a better grasp of vocabulary were able to predict more word meanings, which led to better reading comprehension. Students with less knowledge about words, on the other hand, had less ability to predict word meanings and less ability to understand texts. The study provides pedagogical implications for English language teachers and curriculum developers.